Kajian Yuridis Pekerja Sektor Informal Dalam Perspektif Keadilan - Christian Rivaldi; Imam Budi Santoso; Wiwin Triyunarti (Prodi Magister Ilmu Hukum Fakultas Hukum Universitas Singaperbangsa Karawang, 2025)
Informal workers in Indonesia have not yet obtained their fundamental rights, which the state is obligated to guarantee. Although they are the largest contributors to the national economy, informal workers continue to face discrimination in terms of wages and social protection, as these aspects are not yet regulated by law. This study aims to advocate for state responsibility in fulfilling and accommodating the rights of informal workers through comprehensive legislation, particularly concerning fair wages and social security. Using a normative juridical method with a statutory approach, this research proposes a renewed concept of inclusive social security for all workers, based on Article 34(2) of the 1945 Constitution, which mandates the state to provide social welfare for all citizens. The proposed model draws inspiration from the United Nations’ Universal Health Coverage (UHC) framework to ensure more equitable protection for Indonesia’s informal labor sector. Keywords: Informal Workers, National Social Security, Universal Health Coverage, Wages.